2014
DOI: 10.1155/2014/276128
|View full text |Cite
|
Sign up to set email alerts
|

3D Assessment of Mandibular Growth Based on Image Registration: A Feasibility Study in a Rabbit Model

Abstract: Background. Our knowledge of mandibular growth mostly derives from cephalometric radiography, which has inherent limitations due to the two-dimensional (2D) nature of measurement. Objective. To assess 3D morphological changes occurring during growth in a rabbit mandible. Methods. Serial cone-beam computerised tomographic (CBCT) images were made of two New Zealand white rabbits, at baseline and eight weeks after surgical implantation of 1 mm diameter metallic spheres as fiducial markers. A third animal acted as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…30 The validity of using an automated, regional registration in the mandible to align longitudinal time points was evaluated in a rabbit model. 31 In this study, an affine Procrustes-based registration method was evaluated for accuracy against fiducial metallic implants, showing correspondence at less than 3 voxel widths. 31 Further studies in patients with Apert’s syndrome with clinical computed tomography data have shown method errors ranging from 0.4 to 0.8 mm for multiple landmarks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 The validity of using an automated, regional registration in the mandible to align longitudinal time points was evaluated in a rabbit model. 31 In this study, an affine Procrustes-based registration method was evaluated for accuracy against fiducial metallic implants, showing correspondence at less than 3 voxel widths. 31 Further studies in patients with Apert’s syndrome with clinical computed tomography data have shown method errors ranging from 0.4 to 0.8 mm for multiple landmarks.…”
Section: Discussionmentioning
confidence: 99%
“…31 In this study, an affine Procrustes-based registration method was evaluated for accuracy against fiducial metallic implants, showing correspondence at less than 3 voxel widths. 31 Further studies in patients with Apert’s syndrome with clinical computed tomography data have shown method errors ranging from 0.4 to 0.8 mm for multiple landmarks. 30 Some structures presumed to be stable in 2-dimensional projections, such as the mandibular canal, may show significant lateral displacement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising animal studies on rat mandibles may be helpful to better understand 2D/3D differences 12 but the growth pattern in animal models may not be analogous to humans. Any shift of an area used as reference can cause a misinterpretation in the amount and direction of growth.…”
Section: Discussionmentioning
confidence: 99%
“…However, anatomical structures reported to be stable on lateral headfilm may not be reliable for 3D analysis that also involves the transverse dimension. 12 …”
Section: Introductionmentioning
confidence: 99%